2020
DOI: 10.1039/c9tc05128g
|View full text |Cite
|
Sign up to set email alerts
|

Image-force effects on energy level alignment at electron transport material/cathode interfaces

Abstract: The work function of substrate can be sharply reduced by ETMs with an image-force induced double dipole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 54 publications
(57 reference statements)
1
16
0
Order By: Relevance
“…In addition to the above-mentioned four Phen derivatives, 4,7-di(9H-carbazol-9-yl)-1,10-phenanthroline (BUPH1) 36 , the ESP of which is smaller than that of BPhen, was used for comparison. Although there have been many reports on the electronic structure and the related interactions between a specific Phen derivative and several metals, there have been few reports on the interactions between several Phen derivatives and a specific metal 26 , 37 , 38 . Bin et al 30 were the first to use three Phen derivatives, and the p -MeO–Phen–Ag complex has been reported to be an excellent electron-injection layer (EIL).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above-mentioned four Phen derivatives, 4,7-di(9H-carbazol-9-yl)-1,10-phenanthroline (BUPH1) 36 , the ESP of which is smaller than that of BPhen, was used for comparison. Although there have been many reports on the electronic structure and the related interactions between a specific Phen derivative and several metals, there have been few reports on the interactions between several Phen derivatives and a specific metal 26 , 37 , 38 . Bin et al 30 were the first to use three Phen derivatives, and the p -MeO–Phen–Ag complex has been reported to be an excellent electron-injection layer (EIL).…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently found that certain organic semiconductor follows the ICT model with an extra displacement of the vacuum level. [ 99,100 ] Chen et al have studied the electrode–BPhen interface and found that the BPhen molecule follows the ICT model with an extra vacuum level shift of ≈1.4 eV. This shift was attributed to double dipole step formed at the interface.…”
Section: Energy‐level Alignment At Electrode–organic Interfacementioning
confidence: 99%
“…As a result, the interface dipole of B2PyMPM is reduced to the same level as that of B3 and B4PyMPM in the vacuum-deposited films. This is also the main reason that the interface dipole of B2PyMPM is much smaller than those of BPhen (−1.4 eV) and BCP (−1.6 eV), 18 , 23 even though the former is less affected by the hydrogen bonding.…”
Section: Results and Discussionmentioning
confidence: 97%
“…One dipole moment formed by the N nuclei and the lone pairs points from the substrate surface to the organic film and the other one formed by their image charges shows the same direction. 16 , 18 The N atoms far away from the substrate contribute little to the interface dipole.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation